2019
DOI: 10.1007/s00268-019-05166-w
|View full text |Cite
|
Sign up to set email alerts
|

Management of Open Abdomen After Trauma Laparotomy: A Comparative Analysis of Dynamic Fascial Traction and Negative Pressure Wound Therapy Systems

Abstract: Background Management of the post‐traumatic open abdomen (OA) using negative pressure wound therapy (NPWT) alone is associated with low rates of primary fascial closure. The abdominal reapproximation anchor (ABRA) system exerts dynamic medial fascial traction and may work synergistically with NPWT to facilitate primary fascial closure. Methods Patients with an OA following trauma laparotomy between 2009 and 2018 were identified from a prospectively maintained institutional database. Patients treated with ABRA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 39 publications
0
35
0
4
Order By: Relevance
“…In total, 13 studies fulfilled the criteria [12][13][14][15][16][17][18][19][20][21][22][23][24]. All included studies are observational cohort studies, and no studies reported on the use of either the Wittmann patch or the ABRA system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 13 studies fulfilled the criteria [12][13][14][15][16][17][18][19][20][21][22][23][24]. All included studies are observational cohort studies, and no studies reported on the use of either the Wittmann patch or the ABRA system.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported on the ABRA system in combination with NPWT [12,13], while 9 reported on meshmediated fascial traction (MMFT) combined with NPWT [14][15][16][17][18][19][20][21][22]. Other types of fascial traction, either by dynamic suture lines [23] or by a self-made silastic tube system, and NPWT [24] were reported in 2 studies.…”
Section: Resultsmentioning
confidence: 99%
“…The principal indicator for an open abdomen is a second look laparotomy; other indicators include vascular injuries, swelling and the risk of abdominal compartment syndrome 23 . Optimisation of the patient's haemodynamic condition between operations can lead to potentially salvaging bowel that once potentially appeared ischaemic 23,24 . The current gold standard for management of an open abdomen is NPWT at a minimum negative pressure; however, there is discussion around this causing bowel damage and further anastomotic complications 24,25 .…”
Section: Ileostomy Formationmentioning
confidence: 99%
“…Optimisation of the patient's haemodynamic condition between operations can lead to potentially salvaging bowel that once potentially appeared ischaemic 23,24 . The current gold standard for management of an open abdomen is NPWT at a minimum negative pressure; however, there is discussion around this causing bowel damage and further anastomotic complications 24,25 . Conversely, a retrospective study concluded that non-open abdomen patients after SMA occlusion more frequently required a further bowel resection at the second look, subsequent short bowel syndrome and a higher incidence of sepsis 24 .…”
Section: Ileostomy Formationmentioning
confidence: 99%
“…The combination of different OAT elements such as vacuum-assisted wound closure and mesh-mediated fascial traction (VAWCM), negative-pressure wound therapy (NPWT) and dynamic fascial sutures (DFS) is associated with the highest frequency of DFC [11,[16][17][18][19]. The purpose is to create synergistic effects of edema reduction and gradual fascial approximation [18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%